Journey to the center of the earth - Verne, Jules 1828-1905 (Barnes & Noble Classics, 2005)
Professor Hardwigg, his nephew Harry, and their guide Hans explore a volcanic crater in Iceland that leads them to the center of the Earth and to incredible and horrifying discoveries